Plasma metals and serum bilirubin levels in workers from manganese-exposed workers healthy cohort (MEWHC). (March 2020) - Ge, Xiaoting; Liu, Zhenfang; Hou, Qingzhi; Huang, Lulu; Zhou, Yanting; Li, Defu; Huang, Sifang; Luo, Xiaoyu; Lv, Yingnan; Li, Longman; Cheng, Hong; Chen, Xiang; et al.
Abstract: Few studies specifically address the possible associations between multiple-metal exposures and liver damage among the occupational population. This study aimed to explore the cross-sectional relationships of plasma metals with liver function parameters. For 571 on-the-spot workers in the manganese-exposed workers healthy cohort (MEWHC), we determined liver function parameters: total bilirubin (TBILI), direct bilirubin (DBILI), indirect bilirubin (IBILI), alanine transaminase (ALT) and aspartate transaminase (AST). Total concentrations of 22 plasma metals were measured by ICP-MS. The LASSO (least absolute shrinkage and selection operator) penalized regression model was applied for selecting plasma metals independently associated with liver function parameters. Multiple linear regression analyses and restricted cubic spline (RCS) were utilized for identifying the exposure-response relationship of plasma metals with liver function parameters. After adjusting for covariates and selected metals, a 1-SD increase in log-10 transformed levels of iron was associated with increases in the levels of TBILI, DBILI and IBILI by 20.3%, 12.1% and 23.7%, respectively; similar increases in molybdenum for decreases in levels of TBILI, DBILI and IBILI by 6.1%, 2.6% and 8.3%, respectively. The effect of a 1-SD increase in plasma copper corresponded decreases of 3.2%, 3.4% and 5.0% in TBILI, AST and ALT levels, respectively. The spline analyses further clarified the non-linear relationships between plasma iron and bilirubin whilst negative linear relationships for plasma molybdenum and bilirubin. Plasma iron was positively whilst plasma molybdenum was negatively associated with increased serum bilirubin levels. Further studies are needed to validate these associations and uncover the underlying mechanisms. Graphical abstract: In the present study, we observed the non-linear positive association between plasma iron and serum bilirubin levels while linear negative relationship between plasma molybdenum and serum bilirubin levels, respectively. Image 1 Highlights: Plasma iron had positively non-linear relationships with serum total bilirubin, direct bilirubin and indirect bilirubin. Plasma molybdenum had negatively linear relationships with serum total bilirubin, direct bilirubin and indirect bilirubin. Plasma copper had negatively linear relationships with serum alanine transaminase and aspartate transaminase. Abstract : We observed the non-linear positive association between plasma iron and serum bilirubin levels while linear negative relationship between plasma molybdenum and serum bilirubin levels, respectively.